ANALISIS CERAI GUGAT KARENA KEKERASAN DALAM RUMAH TANGGA DI PENGADILAN AGAMA KABUPATEN JOMBANG TAHUN 2022 - Muhammad Iqbal Abdurrauf; Masrokhin Masrokhin (Kampus Akademik Publiser, 2024)
Domestic Violence (KDRT) is a violation of human rights and a crime against human dignity as well as a form of discrimination against individuals. The increase in domestic violence cases in society has resulted in the number of divorce cases filed by wives at the Religious Courts also increasing.The objectives of this research include: 1) knowing the factors underlying divorce due to domestic violence (KDRT) accepted by the Jombang Regency Religious Court in 2022; 2) find out the forms and causes of domestic violence (KDRT) in the Jombang Regency Religious Court in 2022; and 3) describe the process of resolving divorce due to domestic violence (KDRT) at the Jombang Regency Religious Court in 2022.The type of research carried out is classified as field research. The object of this research is an analysis of divorce due to domestic violence at the Jombang Regency Religious Court in 2022. Meanwhile, the research subjects are the chairman, judge and clerk of the Jombang Regency Religious Court. Data collection techniques were carried out by means of interviews and documentation. The data analysis techniques used in this research are qualitative descriptive analysis and inductive methods.The dominant factors causing divorce are economic factors and a lack of harmony (continuous quarrels and disputes). This shows that the main reason for divorce at the Jombang Regency Religious Court is economic factors, then there is a lack of harmony or continuous quarrels and disputes, followed by domestic violence.The research results showed that data obtained from research at the Jombang Regency Religious Court showed that there were an estimated 219 cases of contested divorce caused by domestic violence. So it can be seen that the percentage of contested divorces due to domestic violence is 8.9% of the total caseload for contested divorces in 2022 at the Jombang Regency Religious Court. It can be concluded that the rate of divorce based on domestic violence is still quite high.